Emotional distress and coping responses to chemotherapy side effects in cancer patients: A systematic review - Zainudin, Zainudin; Haryanto, Haryanto; Suriadi, Suriadi (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Abstract Background: Chemotherapy is a primary treatment modality for cancer patients; however, it is frequently associated with various side effects that significantly affect patients’ physical, psychological, and social well-being. These side effects influence not only treatment outcomes but also patients lived experiences during therapy. Understanding patients’ experiences is essential for improving patient-centred cancer care. Purpose: To explore cancer patients’ experiences related to chemotherapy side effects based on recent scientific evidence. Method: A systematic literature review was conducted using Google Scholar and PubMed databases. Articles published between 2019 and 2024 that focused on cancer patients’ experiences of chemotherapy side effects were selected according to predefined inclusion and exclusion criteria. Results: Twenty eligible studies were included. The findings revealed that chemotherapy side effects are experienced multidimensionally, including physical symptoms, psychological distress, social limitations, and spiritual coping, which collectively affect patients’ quality of life. Conclusion: Chemotherapy side effects profoundly influence cancer patients’ experiences beyond physical symptoms. Holistic and patient-centred care approaches are essential to address these complex needs. Keywords: Cancer; Chemotherapy; Patient Experience.